Marriage Agreements in Indonesia: A Comparative Analysis of Civil Law and Islamic Law after the Constitutional Court Decision - Asrizal Saiin (Indonesian Journal of Law and Syariah, 2025)
Marriage agreements play a strategic role in regulating the rights and obligations of spouses, particularly in relation to the ownership and management of property. This study aims to examine the differences in the regulation of prenuptial agreements under the Indonesian Civil Code (KUH Perdata) and the Compilation of Islamic Law (KHI), and to analyze the impact of the Constitutional Court Decision No. 69/PUU-XIII/2015 on the practice of marriage agreements in Indonesia. The research employs a normative juridical method using statutory and case study approaches, supported by literature reviews of relevant regulations, court rulings, and academic sources. The findings reveal that the Civil Code requires formal notarized agreements, while the KHI offers greater flexibility as long as the agreements align with sharia principles. The Constitutional Court’s decision broadens access to prenuptial arrangements but also brings administrative challenges and a lack of public awareness. This study highlights the importance of harmonizing national legal systems and religious norms to ensure fairer protection, particularly for women in marriage.